THE MODEL OF ORGANIZATION OF MANAGEMENT COUNCILS IN HIGHER EDUCATION INSTITUTIONS - Yakubov Azizjon Tojiboyevich (American Journals Publishing, 2024)
Higher education institutions play an important role in improving the quality of education and ensuring innovative development in modern society. Boards of directors are important in the strategic planning, decision-making and resource management processes of higher education institutions. This article examines the model of organization of management councils in higher education institutions, analyzes its main tasks, composition and ways to improve its effectiveness.
Keywords: Higher education institutions, management board, model, material resources, financial results, educational resources.